REVIU LITERATUR TENTANG KETERAMPILAN PROSES SAINS - Ni Nyoman Sri Vutu Verawati; Saiful Prayogi; Muhammad Asy’ari (Lensa: Jurnal Kependidikan Fisika, 2014)
This article describes scientific learning that focuses on the implementation of learning on scientific principles to build students' thinking skills in accordance with the 2013 curriculum. The essence of science education becomes the main foundation of the importance of teaching science process skills in learning. Scientific skills that are important to train learners in conducting scientific activities. These skills include, 1) observing; 2) interpret; 3) predict; 4) using tools and materials; 5) apply the concept; 6) planning research; 7) communicate.